Prostaglandin E2 and BDNF levels in rat hippocampus are negatively correlated with status epilepticus severity: No impact on survival of seizure-generated neurons - Maria Antonietta Ajmone-Cat; Robert E. Iosif; Christine T. Ekdahl; Zaal Kokaia; Luisa Minghetti; Olle Lindvall (Neurobiology of Disease, 2006)
Partial and generalized status epilepticus (pSE and gSE) trigger the same level of progenitor cell proliferation in adult dentate gyrus, but survival of new neurons is poor after gSE. Here, we show markedly elevated levels of prostaglandin E2 (PGE2) and brain-derived neurotrophic factor (BDNF) in rat hippocampal formation at 7 days following pSE but not gSE. Administration of the cyclooxygenase (COX) inhibitor flurbiprofen for 1 week, starting at day 8 post-SE, abated PGE2 and decreased BDNF levels, but did not affect survival of new neurons 4 weeks later. Thus, high PGE2 and BDNF levels induced by pSE are probably not of major importance for survival of new neurons during the first days after formation. We propose that they modulate other aspects of synaptic and cellular plasticity, and thereby may influence epileptogenesis.